(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
This study deals with an issue closely related to people’s daily lives during their financial transactions and social relations, a phenomenon of forbidden gain that is transferred from the ownership of the owner to a new property in some form of transfer of ownership contracts. Where the research was divided into five paragraphs, the first paragraph dealt with the meaning of the rule, the second paragraph dealt with the legitimate document of this rule of the hadith, and the third paragraph dealt with some of the images reached in the books of jurisprudence and built on this rule, and the fourth paragraph dealt with talk about The sayings of the jurists in the treatment of individuals who earn illegally , through the presentation of doctrinal statements in the matter without exposure to evidence; This is not the subject of our research, and dealt with the fifth paragraph talk about the application of the rule of jurisprudence in contemporary transactions; the most important images in which we can apply this rule: the gain arising from career exploitation, the transformation of commercial financial institutions to Islamic financial institutions, and the gain arising from institutions Financial business, this kind of graft. What is the impact of the application of this rule in the removal of the prohibition?